Efek Anti Hiperlipidemik Ekstrak Etanol Daging Buah Semangka Merah (Citrullus Lanatus) Terhadap Kadar Low Density Lipoprotein Pada Tikus Jantan Galur Wistar (Rattus Norvegicus) - Arsyad Parama Santosa; Indarti Trimurtini; Khomaini Hasan (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2018)
Multiple research assessments have revealed that red watermelons (Citrullus lanatus) contain antioxidants and other active compunds capable of lowering the amount of low-density lipoprotein cholesterol, or LDL-c, in the blood. An elevated lipid profile increases cardiovascular risk factors such as hyperlipidiemia and formation of atherosclerotic plaque. Antioxidants that can reduce cholesterol levels include lycopene and flavonoid, which inhibit HMG-CoA reductase of the mevalonate pathway. In an attempt to gain a more comprehensive understanding of these mechanisms, extract from the pulp of a red watermelon was fed to 3 test groups using 24 hyperlipidemic white wistar rats with various doses (500 mg/kgBW, 750 mg/kgBW, dan 1000 mg/kgBW). Blood samples were conducted before and after administration of the watermelon extract and the LDL-c levels were analyzed statistically. The analysis showed that the LDL-c of each test group decreased signifcantly after administration of watermelon extract (p<0,05) with the highest average decrease coming from the group fed with a dose of 750 mg/kgBW extract (30,58 ± 6,30 mg/dL). However the dose most effective in decreasing LDL-c was 1000 mg/kgBW (p=0,092). Based on these results, it can be concluded that consumption of red pulp watermelon extract decreases LDL-c levels, thus lowering cardiovascular risk factors.